Extracting lessons from an inconclusive history: public policy for adolescents in Serra/ES - - Mara Rejane Barroso Barcelos; Luiz Carlos Fadel de Vasconcellos; Simone Cynamon Cohen (Universidade de Fortaleza, 2012)
Objective: To present a critical-historical report of the Adolescent Citizen Program, a public policy established in 2007 in the municipality of Serra-ES, Brazil. Case description: The lack of space and broad public policies for social integration of young people expressed especially by the lack of vacancies offered in high school and vocational education and lack of policies to encourage the sport, leisure and culture, a reality in the city Serra in 2005. In 2006, the municipal administration conducted a qualitative and quantitative research among adolescents aged 10 to 19 years and from this diagnosis, planned and implemented a policy aimed at that audience. Qualitative methodology focused on the case study, from the standpoint of history and organization, from its monitoring and empirical observation, document analysis and literature review. We describe the national and local political context in which occurred the beginning and implementation of the policy, how and why it was created, its characteristics, proposals, initial results and also approaching its extinction. We analyze if the mechanisms used to delineate it were enough to guarantee its continuity. Conclusion: The program was discontinued with the change of municipal administration, indicating insufficient mechanisms for consolidation of the policy.